If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 + -20 = 2p Combine like terms: 42 + -20 = 22 22 = 2p Solving 22 = 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. 22 + -2p = 2p + -2p Combine like terms: 2p + -2p = 0 22 + -2p = 0 Add '-22' to each side of the equation. 22 + -22 + -2p = 0 + -22 Combine like terms: 22 + -22 = 0 0 + -2p = 0 + -22 -2p = 0 + -22 Combine like terms: 0 + -22 = -22 -2p = -22 Divide each side by '-2'. p = 11 Simplifying p = 11
| 3y^2-4=4y | | -4x-40-14x=32 | | C=Amt | | C=Amy | | x-x*0.2=y | | 3x^2-14x=5 | | 4k(k+3)=-19 | | 3-2=x+4 | | 5x+2(x+2)=18 | | 6x^2+11x=72 | | 4x^2-44x=-120 | | 3x+6=X+4 | | C=2500+0.5Yd | | 14+8.2= | | -2j+5=6h | | 3u-(25-u)=-11-2u | | Y=3mx-4b | | t^4-13t^2+36=0 | | (x-1)(2x+1)=0 | | 320=24+20 | | x^2+28x+5=0 | | y^2+16y+28=0 | | 6x^2-9-13x^2+11+11x= | | 3p+3=14 | | 12+(34-5)= | | 3(x+8)=15 | | -16x=-48 | | 5x^2-5=0 | | x-3x=8 | | 8x-9=7x-3 | | 9.4m= | | 0.5(3x+2)-0.2(x+6)=5 |